The NLRP3 Inflammasome Inhibitor Dapansutrile Attenuates Cyclophosphamide-Induced Interstitial Cystitis - Kiran, Sonia; Rakib, Ahmed; Singh, Udai P. (Frontiers in Immunology, 2022)
Interstitial cystitis (IC)/bladder pain syndrome (BPS), hereafter referred to together as IC, is a clinical syndrome characterized by sterile inflammation in the bladder. While the etiology and pathophysiology of IC remain unclear, it may involve autoimmunity in light of the significant role played by the NLRP3 inflammasome. However, the effect on IC of NLRP3 inhibitors including dapansutrile (Dap) had not been explored previously. Here, we investigated the effect of Dap in the cyclophosphamide (CYP)-induced experimental mouse model of IC, which results in functional and histological alterations confined to the urinary bladder (UB) comparable to that of clinical IC. CYP-induced mice treated with Dap exhibited improved UB pathology and reductions in inflammation scores and the frequency and the number of mast cells and neutrophils, relative to mice that received CYP alone. Dap- and CYP-treated mice also exhibited infiltration of T cells in the spleen and iliac lymph nodes (ILNs) and a concurrent significant decrease (p<0.01) in CXCR3+CD8+ T cells in the UB, induction of systemic and mucosal dendritic cells (DCs), and reduced levels of systemic proinflammatory cytokines, as compared to CYP alone. We also observed decreases in the expression of several signaling pathways regulators, including interleukin-1 beta (IL-1), NLRP3, caspase-1, nuclear factor kappa B (NF-B), and inducible nitric oxide synthase (iNOS) in the UB of CYP- and Dap-treated mice, relative to those receiving CYP alone. Taken together, these results suggest that Dap suppresses IC through the reduction of CXCR3+T cells, mast cells, and neutrophils in the UB and induces DCs as a protective measure. The present study identifies the mechanisms underlying the amelioration of IC by the NLRP3 inhibitor Dap and may provide an avenue for a potential therapeutic agent for the treatment of IC.